Penerapan Metode Six Sigma sebagai Usaha untuk Memperkecil Kecacatan Produk Fraypan Merek Revere Were di CV. Corning Sidoarjo - Boy Isma Putra (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
CV. Corning Sidoarjo is a home furnishings industry, one product is kitchen furniture brand Revere Was able to produce as many as ± 34.152 units per year. Production conditions of Revere Ware brand products now has the highest number of defective products within each sub process: press, press cutting (cut), roll process, and mashed process 2.436 units per year or approximately 7.13% of total production per year. Based on these data, CV. Corning Sidoarjo trying to reduce the defect rate of products by determining the performance of initial conditions (baseline) and performance targets to be achieved by using Six Sigma methods. With Six Sigma methods can be obtained performance targets aimed at reducing the level of defects in each sub-process, namely: The process of pressing, the process of cutting, coil processing, and mashed process of 2.292 units per year or approximately 6.71% of total production per year.